2018
DOI: 10.1016/j.rser.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in energy attitudes and perceptions: Evidence from Europe

Abstract: Driven by socioeconomic processes, the influence of spatial factors on household energy related attitudes and perceptions is largely neglected in the literature. This paper analyses the extent to which energy perceptions and attitudes vary across different geographical contexts in Europe. We use representative Eurobarometer survey data to analyze how social conceptions of important energy issues, Europe's future energy priorities, and future energy system characteristics are shaped by rural, small urban, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
1
12
1
1
Order By: Relevance
“…They found that there is a positive relationship between environmental concern and intention to adopt EEMs, which coincide with results from previous studies [55,56]. Although attitude seems to be an essential determinant to explain the intention to adopt and WTP for EEMs [32,50,57], environmental and socio-demographic variables (geographical context, income level, education, gender and age of household) have an influence, too [31,32,35,58].…”
Section: Perception and Attitudessupporting
confidence: 82%
See 3 more Smart Citations
“…They found that there is a positive relationship between environmental concern and intention to adopt EEMs, which coincide with results from previous studies [55,56]. Although attitude seems to be an essential determinant to explain the intention to adopt and WTP for EEMs [32,50,57], environmental and socio-demographic variables (geographical context, income level, education, gender and age of household) have an influence, too [31,32,35,58].…”
Section: Perception and Attitudessupporting
confidence: 82%
“…Price premium [26] Does the housing market value energy efficient homes? Evidence from the energy star program USA [27] Energy efficiency and economic value in affordable housing Netherlands [28] Green signalling effects in the market for energy-efficient residential buildings Finland [29] A comparative study of theoretical behaviour change models predicting empirical evidence for residential energy conservation behaviours Global Consumer´s perspective, willingness to pay [30] Beyond energy efficiency and individual behaviours: policy insights from social practice theories Global [31] Spatial variation in energy attitudes and perceptions: Evidence from Europe EU [32] Determinants of Southern Italian households' intention to adopt energy efficiency measures in residential buildings Italy [33] Willingness to pay for energy-saving measures in residential building Switzerland [34] Behavior Driven Energy Efficiency: A Customized Feedback Approach USA [35] U.S. consumer attitudes and expectations about energy USA [3] Risk preferences and purchase of energy-efficient technologies in the residential sector USA [36] New homebuyers and the challenges of navigating sustainability and energy efficiency with Australian volume builders [43] Energy efficiency services for residential buildings: market situation and existing potentials in the European Union EU [44] Is energy efficiency capitalized into home prices? Evidence from three U.S. cities USA [45] Economic returns to energy-efficient investments in the housing market: Evidence from Singapore Singapore…”
Section: Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [14][15][16] demonstrated that consumer perceptions about renewable energy often vary by country. Even within a country studies [17,18] showed that those in rural areas are more likely to invest in renewable energy than those in urban areas. Other studies [19,20] noted that different lifestyles affect technological choices.…”
Section: Introductionmentioning
confidence: 99%